Konsep dan pelaksanaan wakaf di Malaysia - Mustapha bin Hj. Nik Hassan (Kuala Lumpur: Institut Kefahaman Islam Malaysia, 1999)
Essays on the concept and implementation of waqf in Malaysia; papers of a seminar.
Includes bibliographical references and index.
Keywords: Waqf -- -- Malaysia; Islam and state -- -- Malaysia; Islamic law -- -- Malaysia